A functional genetic approach identifies the PI3K pathway as a major determinant of trastuzumab resistance in breast cancer - Berns, Katrien; Horlings, Hugo M; Hennessy, Bryan T; Madiredjo, Mandy; Hijmans, E Marielle; Beelen, Karin; Linn, Sabine C; Gonzalez-Angulo, Ana Maria; Stemke-Hale, Katherine; Hauptmann, Michael; Beijersbergen, Roderick L; Mills, Gordon B; et al. (Cancer cell, 2007)
A large-scale RNA interference screen to discover genes involved in trastuzumab resistance in breast cancer identified only PTEN as a modulator of drug sensitivity. Oncogenic mutants of PIK3CA (activator of the same pathway and frequently mutated in breast cancer) also conferred resistance to trastuzumab in cell culture. In a cohort of 55 breast cancer patients, activation of the PI3K pathway, as judged by the presence of oncogenic PIK3CA mutations or low PTEN expression, was associated with poor prognosis after trastuzumab therapy, and the combined analysis of PTEN and PIK3CA identified twice as many patients at increased risk for progression compared to PTEN alone. Thus, assessment of PI3K pathway activation may provide a biomarker to identify patients unlikely to respond to trastuzumab-based therapy.